Preparation of Inulin Powder from Dioscorea Esculenta Tuber with Foam Mat Drying Method - , Eni Harmayani ([Yogyakarta] : BITEC Bangna, 2011)
Inulin is a natural nondigestiblefructooligosaccharidethat occurs as a reserve carbohydrate in several plants. Currently, chicory is an excellent source of inulin. However, chicory is a plant that grown primarily in Europe. Lesser yam (Dioscorea esculenta) is one of local tuber that has potential as a source of inulin. Our previous study indicated that higher amount of inulin could be extracted from Dioscorea esculenta as compared with the other tubers. This research was conducted to study the production of inulin powder from lesser yam using foam mat drying method. The specific objective of the study was to examine the effect of filler types (dextrin, maltodextrin,Na-CMC) and foaming agent concentration (2- 10% of egg white) on the yield and characteristic of the inulin powder. Inulin was prepared by the following method. Lesser yam was mixed with hot water at 90&deg